They built this city-construction workers injured in Delhi, India: cross-sectional analysis of First Information Reports of the Delhi Police 2016-2018 - Phil Edwards; Sajjan Yadav; Jonathan Bartlett; John Porter (BMC, 2022)
Abstract Background Construction workers are 3-4 times more likely than other workers to die from accidents at work-however, in the developing world, the risks associated with construction work may be 6 times greater. India does not publish occupational injury statistics, and so little is known about construction workers injured. We aimed to use Indian police records to describe the epidemiology of construction site injuries in Delhi and to thus generate knowledge that may help to control the burden of injuries to construction workers in India and in other developing countries. Methods This was a cross-sectional analysis of accident records maintained by the Delhi Police. We included all construction workers reported to have been killed or injured in construction site accidents in Delhi during the period 2016-2018. We used multivariable logistic regression models to investigate associations between injury severity (fatal vs. non-fatal injury) and exposure variables whilst adjusting for a priori risk factors. We also estimated the number of Delhi construction workers in total and by trade to generate estimates of worker injury rates per 100,000 workers per year. Results There were 929 construction site accidents within the study period, in which 1,217 workers and children were reported to have sustained injuries: 356 (29%) were fatal and 861 (71%) were non-fatal. One-eighth of injuries were sustained by females. Most occurred in the Rainy season; most were sustained during the construction of buildings. The most frequent causes were the collapse of an old building, the collapse of a new building under construction, and electric shocks. Electricians were more likely than unskilled workers to suffer a fatal injury (adjOR 2.5; 95% CI: 0.87-6.97), and there were more electrical shocks than electricians injured. The odds of a fatal injury were statistically significantly lower in Central districts than in the less developed, peripheral districts. Conclusions Construction site injuries are an unintended health impact of urbanisation. Women undertake manual work alongside men on construction sites in Delhi, and many suffer injuries as a consequence: an eighth of the injuries were sustained by females. Children accompanying their working parents on construction sites are also at risk. Two main hazards to construction workers in Delhi were building collapses and electrical shocks. Electricians were over twice as likely as unskilled workers to suffer a fatal injury, and electrical work would appear to be undertaken by a multitude of occupations. As the global urban population increases over the coming decades, so too will the burden of injuries to construction workers. The introduction and enforcement of occupational safety, health, and working conditions laws in India and in other rapidly developing countries will be necessary to help to control this injury burden to construction workers.